2020
DOI: 10.1021/acsami.0c17975
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Elastic Properties, and the Li Transport Mechanism of the Protonated and Fluorinated Antiperovskite Lithium Conductors

Abstract: Lithium-rich antiperovskites (APs) have attracted significant research attention due to their ionic conductivity above 1 mS cm −1 at room temperature. However, recent experimental reports suggest that proton-free lithium-rich APs, such as Li 3 OCl, may not be synthesized using conventional methods. While Li 2 OHCl has a lower conductivity of about 0.1 mS cm −1 at 100 °C, its partially fluorinated counterpart, Li 2 (OH) 0.9 F 0.1 Cl, is a significantly better ionic conductor. In this article, using density func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 70 publications
(182 reference statements)
7
56
0
Order By: Relevance
“…30 And theoretical calculations also demonstrated that the formation energy of Li 2 OHCl from LiOH + LiCl is significantly lower than that of Li 3 OCl. 65 However, the calculated value of formation energy of Li 2 OHCl is positive, meaning that Li 2 OHCl is also thermodynamically unstable. It is easy to obtain the Li 2 OHCl with LiCl-deficient experimentally, and hence it is more stable than the ideal Li 2 OHCl crystal.…”
Section: Phase Stabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…30 And theoretical calculations also demonstrated that the formation energy of Li 2 OHCl from LiOH + LiCl is significantly lower than that of Li 3 OCl. 65 However, the calculated value of formation energy of Li 2 OHCl is positive, meaning that Li 2 OHCl is also thermodynamically unstable. It is easy to obtain the Li 2 OHCl with LiCl-deficient experimentally, and hence it is more stable than the ideal Li 2 OHCl crystal.…”
Section: Phase Stabilitymentioning
confidence: 98%
“…In addition, the mismatch of the ionic sizes between F À , OH À , and Cl À (1.33 Å, 1.37 Å, and 1.81 Å, respectively) causes the local structural distortions that enlarged the Li + migration channels close to the F atom. 65…”
Section: Dynamics Of H or Oh Group In Lithium Halide Hydroxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies investigated alloying as a way to induce site distortion in anti-perovskites. For instance, Effat et al attributed the faster conduction of fluorinated Li 2 OHCl in part to distortion of sites upon substitution of F − for Cl − , which flattens out the energy minima in the landscape [65]. Chen et al found the same distortion-induced frustration effect could be prompted by incorporating Br − on the Cl − site in Li 3 OCl 1−x Br x [66].…”
Section: (B) Site Distortion and Anion Packingmentioning
confidence: 99%
“…For instance, Effat et al. attributed the faster conduction of fluorinated in part to distortion of sites upon substitution of for , which flattens out the energy minima in the landscape [ 65 ]. Chen et al.…”
Section: Structural Frustrationmentioning
confidence: 99%